The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/bi101411q
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin-like Protein from Entamoeba histolytica: Solution Structure and Calcium-Binding Properties of a Partially Folded Protein

Abstract: The mechanism of Ca(2+)-signaling in the protozoan parasite Entamoeba histolytica is yet to be understood as many of the key regulators are still to be identified. E. histolytica encodes a number of multi-EF-hand Ca(2+)-binding proteins (EhCaBPs). Functionally only one of these molecules, EhCaBP1, has been characterized to date. The calmodulin-like protein from E. histolytica (abbreviated as EhCaM or EhCaBP3) is a 17.23 kDa monomeric protein that shows maximum sequence identity with heterologous calmodulins (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 53 publications
4
17
0
Order By: Relevance
“…Three dimensional structure, using nuclear magnetic resonance (NMR) spectroscopy, suggests that EhCaBP3 has a well folded N-terminal domain and an unstructured C-terminal counterpart, somewhat similar to calmodulin and EhCaBP1. Interestingly, EhCaBP3 was found in all three major cellular compartments; nucleus, cytoplasm and membrane [35]. In this report we show that EhCaBP3 is involved in the process of phagocytosis at both initiation and phagosome formation stages.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Three dimensional structure, using nuclear magnetic resonance (NMR) spectroscopy, suggests that EhCaBP3 has a well folded N-terminal domain and an unstructured C-terminal counterpart, somewhat similar to calmodulin and EhCaBP1. Interestingly, EhCaBP3 was found in all three major cellular compartments; nucleus, cytoplasm and membrane [35]. In this report we show that EhCaBP3 is involved in the process of phagocytosis at both initiation and phagosome formation stages.…”
Section: Introductionmentioning
confidence: 53%
“…We have earlier shown the involvement of one of the calcium sensing CaBPs of E. histolytica , EhCaBP1 in erythrophagocytosis [19], [21]. EhCaBP3 was identified as a calmodulin-like calcium binding protein of E. histolytica as its structure showed similarity with calmodulin [35]. Since multiple CaBPs are likely to be involved in different steps of phagocytosis, the subcellular localization of EhCaBP3 was checked during RBC uptake by immunostaining with specific anti-EhCaBP3 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the domains is formed by a pair of EF-hands, usually separated by a flexible linker, which could be extended in forming classical dumbbell structures seen for CaM and troponin C. The structural characterization of EhCaBP1 and EhCaBP2 revealed presence of two-domain structures with four EF-hands [34,35]. On the other hand, EhCaM (EhCaBP3) was shown to possess a pair of EF-hands (EF-I and EF-II) in its NTD and a completely unstructured CTD having a lone unpaired non-canonical EF-hand (EF-III) [36]. The NMR derived 3D-structure of EhCaBP6 showed that EhCaBP6 has one unusual (EF-I; D23-Q34), one canonical (EF-III; D96-D107) and two non-canonical (cryptic) (EF-II and EF-IV) EF-hands.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such a large number of CaBPs in this organism suggests that E. histolytica has an intricate and extensive Ca 2ϩ signaling system. Three of these proteins: EhCaBP1 (PDB code 1jfk) (8), EhCaBP2 (PDB code 2jnx) (9) and EhCaM (PDB code 2lc5) (10) have been structurally characterized by NMR in our laboratory and were shown to have unique individual properties. EhCaBP1 has been studied more extensively and its role in phagocytosis has been deciphered (8, 10 -12).…”
mentioning
confidence: 99%